The Influence Of Technology Acceptance Model On The Purchasing Interest Of The Kefamenanu Community On E-Commerce Shopee - Fredirikus Timo; Emilia Khristina Kiha; Rikhardus Bria Seran (SEAN Institute, 2024)
Interest in buying in a way on line influenced by convenience or trust consumer to something marketplace . This matter caused by the system one of them is information is Technology Acceptance Model (TAM). TAM consists from perceived ease of use ( ease use ), perceived usefulness ( usefulness ), attitude toward using technology ( attitude ), behavioral intention to use ( intention ), and actual technology use ( use real technology ) . Study This focuses on convenience users and trust consumers on one marketplace namely Shopee. The purpose of study This For know influence factor convenience users ( perceived ease of use ) towards interest buy public Famenanu on e-commerce Shopee, influence factor trust ( perceived trust ) towards interest buy public Kefamenanu on e-commerce Shopee as well influence factor convenience users and trust to interest buy public Famenanu on e-commerce Shopee. Method used in study This is TAM method and data collection using distributed questionnaires to 75 respondents in a way direct as well as Validity and reliability tests were carried out which resulted all items used in questionnaire said to be valid and reliable . Research methods using the t test and f test with help IBM SPSS Statistics software . Research result show convenience user influential to interest buy and trust influential to interest buy . Whereas For convenience users and trust are also the same influential to interest buy.